1996
DOI: 10.1007/bf00198141
|View full text |Cite
|
Sign up to set email alerts
|

Water molecule binding and lifetimes on the DNA duplex d(CGCGAATTCGCG)2

Abstract: Measurements of the water proton spin-lattice relaxation rate for aqueous solutions of the palindromic dodecamer, d(CGCGAATTCGCG)2, are reported as a function of the magnetic field strength. The magnitude of the relaxation rates at low magnetic field strengths and the shape of the relaxation dispersion curve permit assessment of the number of water molecules which may be considered bound to the DNA for a time equal to or longer than the rotational correlation time of the duplex. The data are examined using lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
0
23
2
Order By: Relevance
“…Within the overlapping range, 1 to 30 MHz, both studies reveal a dispersion with an amplitude much smaller than usually found for proteins. In contrast to Zhou & Bryant (1996), we argue that this dispersion is due to labile DNA protons rather than to long-lived water molecules. In particular, our ®nding that netropsin binding does not eliminate this dispersion (Figure 11), conclusively demonstrates that it cannot be due to water molecules in the minor groove.…”
Section: Comparison With Previous Studiescontrasting
confidence: 57%
See 2 more Smart Citations
“…Within the overlapping range, 1 to 30 MHz, both studies reveal a dispersion with an amplitude much smaller than usually found for proteins. In contrast to Zhou & Bryant (1996), we argue that this dispersion is due to labile DNA protons rather than to long-lived water molecules. In particular, our ®nding that netropsin binding does not eliminate this dispersion (Figure 11), conclusively demonstrates that it cannot be due to water molecules in the minor groove.…”
Section: Comparison With Previous Studiescontrasting
confidence: 57%
“…Finally, we comment on a 1 H NMRD and NOESY study, of the same dodecamer as studied here, that appeared in print after the completion of this work (Zhou & Bryant, 1996). The 1 H NMRD pro®le reported by these authors extends up to 30 MHz, as compared to 600 MHz here.…”
Section: Comparison With Previous Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…[29], the integral of J() is generally larger than that of the reference Lorentzian, so that 0 Ն ͗ C ͘.…”
Section: J͑0͒mentioning
confidence: 99%
“…Well-documented cases include a study of poly (methacrylic acid) (Glasel, 1970) and a recent study of an oligonucleotide (Zhou and Bryant, 1996). In both cases, subsequent studies revealed that the relaxation effects that had been attributed to hydration water were entirely due to labile hydrogens (Halle and Piculell, 1982;Denisov et al, 1997a).…”
Section: Labile Hydrogensmentioning
confidence: 99%